Deformed wing virus of honey bees is inactivated by cold plasma ionized hydrogen peroxide - Cook, Steven C.; Ryabov, Eugene V.; Becker, Christian; Rogers, Curtis W.; Posada-Florez, Francisco; Evans, Jay D.; Chen, Yan Ping (Frontiers in Insect Science, 2023)
Deformed wing virus (DWV) is a widespread pathogen of Apis mellifera honey bees, and is considered a major causative factor for the collapse of infected honey bee colonies. DWV can be horizontally transmitted among bees through various oral routes, including via food sharing and by interactions of bees with viral-contaminated solid hive substrates. Cold plasma ionized hydrogen peroxide (iHP) is used extensively by the food production, processing and medical industries to clean surfaces of microbial contaminants. In this study, we investigated the use of iHP to inactivate DWV particles in situ on a solid substrate. iHP-treated DWV sources were ~105-fold less infectious when injected into naïve honey bee pupae compared to DWV receiving no iHP treatment, matching injected controls containing no DWV. iHP treatment also greatly reduced the incidence of overt DWV infections (i.e., pupae having >109 copies of DWV). The level of DWV inactivation achieved with iHP treatment was higher than other means of viral inactivation such as gamma irradiation, and iHP treatment is likely simpler and safer. Treatment of DWV contaminated hive substrates with iHP, even with honey bees present, may be an effective way to decrease the impacts of DWV infection on honey bees.